A new stonefly from Lebanon, Leuctra cedrus sp. n. (Plecoptera: Leuctridae) - Vinçon, Gilles (Illiesia, 2014)
Leuctra cedrus, is described from Lebanon. In the Leuctra hippopus group it clearly differs from the previously known species by the shape of the male dorsal ornamentations and genitalia. L. cedrus sp. n. is a cold stenothermal species occurring in the close surrounding of rheocrene karstic springs on the Western slope of Mount Lebanon. The list of the 17 stoneflies species known from Lebanon is updated.
Keywords: entomology; Leuctra cedrus; Lebanon; Plecoptera; new species